The Principles Upon Which The Islamic Civilization Was Built: How To Employ Them In Countering Violent Extremism And Terrorism - Alhashmi , Eiman Ahmed Khaleel (AL-WIJDÃN Journal of Islamic Education Studies, 2023)
The Islamic civilization was built upon the noble religious teachings, which aimed at honoring humans, preserving their lives, and ensuring their safety and prosperity. However, the peace of our societies has been tainted by the rise in extremist ideologies and terrorism. This study analyzed the foundation and principles upon which Islamic civilization was built, highlighting five key principles, namely; seeking knowledge, universality of religion, humanity, tolerance, and equality. The reasons behind the rise in violent extremism and terrorism we see in our Muslim communities were analyzed, shedding light upon seven core reasons. The study found that there are four key players that are critical in mobilizing the principles of Islamic civilization in combatting violent extremisms and terrorism: the family, the universities, the regulatory institutions, and the media agencies. Recommendations were developed based on the role of each in promoting and instilling Islamic principles.   Keywords: Islamic Principles, Muslim Civilization, Violent Extremism, Terrorism, Humanity, Tolerance, Media, Youth.